Spontaneous Hair Repigmentation in an 80-Year-Old Man: A Case of Melanoma-Associated Hair Repigmentation and Review of the Literature. (September 2019) - Chan, Cynthia; Magro, Cynthia M.; Pham, Anh Khoa; LeBlanc, Robert E.; Yan, Shaofeng; Barton, Dorothea T.; Pace, Nicole C.; Chapman, M. Shane; Momtahen, Shabnam
Abstract : Abstract: Spontaneous hair repigmentation of physiologically white or gray hair is a rare occurrence that may be associated with melanoma in elderly individuals. We present the first case of this phenomenon in a man. A gray-haired, 80-year-old man presented to dermatology clinic with a 3-cm lock of black hair on his vertex scalp that developed over 1 year. Punch biopsies showed an increase in junctional dendritic melanocytes with rare pagetoid cells and extension along the follicular outer root sheath epithelium and interfollicular epidermis, associated with prominent dendritic melanocytic hyperplasia and pigment-containing melanocytes within the hair bulbs. Although the findings on the biopsies were not diagnostic of melanoma in situ, an irregular interfollicular distribution of melanocytes was concerning for an adjacent atypical process. A complete excision was performed and revealed melanoma in situ, lentigo maligna type. Rare reports describe spontaneous hair repigmentation as a harbinger of lentigo maligna in women. Repigmentation can occur in the setting of proliferation of malignant pigment-producing melanocytes or by paracrine stimulation of benign bulbar melanocytes through receptor tyrosine kinase KIT activation. Presence of prominent dendritic melanocytic hyperplasia and pigment-containing melanocytes within the hair bulbs in our patient's biopsies was suggestive of paracrine or physiologic stimulation of bulbar melanocytes. Given the importance of early melanoma detection and the low visibility of the scalp, this report raises awareness of an extraordinary presentation of lentigo maligna and exemplifies the importance of close clinicopathologic correlation to ensure optimal clinical management and patient outcome.